Analysis of Science Teachers' Difficulties in Developing Learning Objectives Flow in Phase D - Aulia Rahmadhani; Meili Yanti (Didaktika: Jurnal Kependidikan, 2024)
In the implementation of the Merdeka Curriculum, particularly in phase D, the Learning Objectives Flow is expected to assist educational units and educators in developing steps or learning pathways based on the established learning outcomes. This research investigates the factors contributing to the difficulties faced by science teachers in developing Learning Objectives Flow in phase D. The study combined the collection of quantitative and qualitative data through a sequential explanatory design. Data was collected through questionnaires and interviews with 18 science teachers from junior high schools in Majene Regency, West Sulawesi Province. According to the findings, the average score of science teachers' ability to develop Learning Objectives Flow in phase D is 73.79, which falls into the moderate category based on quantitative data analysis. Based on the qualitative data analysis from interviews, it was found that science teachers face difficulties in developing Learning Objectives Flow for science based on the following aspects: (1) understanding of learning outcomes for science; (2) ability to formulate learning objectives for science; (3) ability to systematically and logically structure the learning objectives flow for science; (4) ability to map the number of lesson hours; and (5) ability to explore the potential/characteristics of the school that support the implementation of learning. For future research, it is hoped to explore efforts that science teachers can make to overcome the difficulties of implementing the Merdeka Curriculum, especially in overcoming difficulties in preparing the Learning Objectives Flow for science in phase D.